(untitled) (Third Sector Social Economic Review, 2024)
Western Balkans and Turkiye are known as enlargement countries because they want to join the European Union. The goal of the Green Deal, which the Western Balkan countries are currently integrating into the European Union Green Deal, is to transition nations from a traditional economic model to a sustainable one. The study’s objective is to investigate, using multi-criteria decision-making techniques, the views of the Western Balkan countries, Turkiye, and the average European Union with respect to the Green Deal criteria. The data used in the study belong to the year 2020 and consist of the performances of the countries according to 10 criteria. The criteria are weighted using the CRITIC method. The attitudes of the countries were compared with the TODIM method. According to the findings, the three most successful countries with higher than European Union average value are Montenegro, Bosnia and Herzegovina and Albania.